QHAPAQ ÑAN ITINERARIO CULTURAL INSCRITO EN LA LISTA DEL PATRIMONIO MUNDIAL, RETOS Y PERSPECTIVAS - Chirinos Portocarrero, Ricardo (2017)
The inscription of the Qhapaq Ñan - Andean Road System in the World Heritage List is the result of a coordinated effort between six Andean countries: Argentina, Bolivia, Colombia, Chile, Ecuador and Peru. The major events of this process are described, as well as the methodological aspects and criteria that were adopted. Furthermore, the Qhapaq Ñan is characterized on a basis of archaeological and anthropological records, outlining the extent and significance of this prehispanic monument. Then, we discuss the implications of the newly inaugurated and World Heritage-acknowledged phase. Specifically, regarding the case of Peru, we assert to the importance of consolidating a management system of the Qhapaq Ñan, through permanent international coordination which incorporates the active participation of local populations, seeking to maximize social benefits, minimize negative impacts and accomplish the commitments made by the Peruvian State before UNESCO. Finally, we present the case of the Project for the Huánuco Pampa – Huamachuco Section, in order to demonstrate how these proposals are being concretely implemented through different lines of action.